Arminian theology : myths and realities - Olson, Roger E. (Downers Grove, IVP Academic, 2006)
Roger Olson sets forth classical Arminian theology and addresses the myriad misunderstandings and misrepresentations of it through the ages. Irenic yet incisive, Olson argues that classical Arminian theology has a rightful place in the evangelical church because it maintains deep roots within Reformational theology, even though it maintains important differences from Calvinism. Myths addressed include: Myth 1: Arminian Theology Is the Opposite of Calvinist/Reformed Theology Myth 2: A Hybrid of Calvinism and Arminianism Is Possible Myth 3: Arminianism Is Not an Orthodox Evangelical Option Myth 4: The Heart of Arminianism Is Belief in Free Will Myth 5: Arminian Theology Denies the Sovereignty of God Myth 6: Arminianism Is a Human-Centered Theology Myth 7: Arminianism Is Not a Theology of Grace Myth 8: Arminians Do Not Believe in Predestination Myth 9: Arminian Theology Denies Justification by Grace Alone Through Faith Alone Myth 10: All Arminians Believe in the Governmental Theory of the Atonement.
Myth 1: Arminian theology is the opposite of Calvinist/Reformed theology -- Myth 2: A hybrid of Calvinism and Arminianism is possible -- Myth 3: Arminianism is not an orthodox evangelical option -- Myth 4: The heart of Arminianism is belief in free will -- Myth 5: Arminian theology denies the sovereignty of God -- Myth 6: Arminianism is a human-centered theology -- Myth 7: Arminianism is not a theology of grace -- Myth 8: Arminians do not believe in predestination -- Myth 9: Arminian theology denies justification by grace alone through faith alone -- Myth 10: All Arminians believe in the governmental theory of the atonement -- Rules of engagement for evangelical Calvinists and Arminians.
Includes bibliographical references and indexes.
Keywords: Arminianism